(untitled) (Revista LIDER, 2020)
The article presented here stems from a qualitative research Project about the social discourse and representations that mapuche williche indigenous leaders elaborate in the regions of Los Lagos and Los Ríos (previously part of the Region de Los Lagos) en relation to Bilingual Intercultural Education (EIB). This project entails the participation of 26 leaders from four zones with a high concentration of indigenous peoples in the areas of Panguipulli (Mariquina, Lanco and Panguipulli); Lago Ranco (Futrono and Lago Ranco); San Juan (San Pablo, Osorno, San Juan de la Costa and Río Negro) and; Chiloé (Ancud, Choncho and Quellón). The processes of analysis are carried out with a hermeneutic approach centered on the identification of Social Representations and the political argumentation generated from the implementationofinterculturaleducational experiences en the school located in these areas. In this text we present and develop conceptual schemes that generate a web of social representations which the leaders appropriate in order to signify their vital and communal experiences producing a political discourse that articulates their traditional demands with the political cultural revindications associated to the schools.